Modern Models of Radio Broadcasting as an Example of the Formatting of Emission Panels - Jarosław Kinal (European Scientific Journal, ESJ, 2018)
Nowdays, the impact of marketing solutions for media system is particularly noticeable in case of the so-called traditional media, ie newspapers, radio and television. With reference to the declining expenditures and audience, publishers of These forms of media, looking for niches allowing survival. In the radio broadcasting sector, the niche is well defined target audience mentally attached this the program or Radio. In the era of market consolidation is often and company has in its portfolio several radio stations with different target groups. This article describes the historical background input radio format and modern scientific definitions of the phenomenon.